COMPARISON OF LYMPHOCYTE AND MONOCYTE COUNTS IN BALI CATTLE (BOS SONDAICUS) BEFORE AND AFTER FOOT AND MOUTH DISEASE VACCINATION - Beatrice Atria Putri Purba; I Nyoman Sulabda; Ni Luh Eka Setiasih (Buletin Veteriner Udayana, 2026)
Bali cattle (Bos sondaicus) are an indigenous Indonesian breed with good resilience to tropical climates, yet they are susceptible to Foot-and-Mouth Disease (FMD). Vaccination is carried out to enhance the immune system, which can be observed through changes in lymphocyte and monocyte counts. This study aimed to compare lymphocyte and monocyte counts before and after FMD vaccination. A total of 15 blood samples from healthy Bali cattle were examined before and after FMD vaccination at Disease Investigation Center Denpasar. Hematological examinations were performed manually using Giemsa-stained blood smear preparations for differential leukocyte counts. Data were analysed using a paired t-test. The results showed that the mean lymphocyte count increased significantly from 43,07 ± 10,559% to 63,47 ± 7,745% (p<0.05). Furthermore, the mean monocyte count also showed a significant increase from 3.60 ± 2,354% to 6,07 ± 2,738% (p<0.05). Thus, FMD vaccination in Bali cattle can stimulate the immune response, primarily the humoral immune response through antibody production, supported by the cellular immune response in combating FMD virus infection.